Workshop Metode Menghapal Al Quran el Talaqqi qu bagi Guru Pendidikan Anak Usia Dini - yessy yanita sari (Jurnal SOLMA, 2021)
Educational institutions such as Early Childhood Education (PAUD) to High School (SMA) have included the Tahfizh Al Quran learning program in the school curriculum. Memorizing the Qur'an is not like memorizing other lessons. In memorizing the Qur'an there are rules that must be considered. The method of memorizing the Qur'an determines the success of students in memorizing the Qur'an. For early childhood method of memorizing the Koran must pay attention to the stages of development of students. This Workshop activity aims to provide knowledge and training on memorizing the Koran method for students, especially early childhood. The workshop was delivered to PAUD teachers who are members of HIMPAUDI Pakuhaji. At the time of the activity it was learned that 74,4% PAUD teachers had been teaching Tahfizul Quran without specific methods. This workshop was considered very useful, so there was a request for further training related to the application of the el Talaqi qu method. Keywords: Tahfizh Al Quran, el Talaqqi qu Method, PAUD